The Relevance of ISO 21001 Implementation to the Enhancement of Islamic Religious Education Learning Quality in Private Islamic Junior Secondary Schools in Mataram City - Raihan, Adi Fadli, Abdul Mujib (Journal of Educational Studies, 2025)
This study examines the relevance of ISO 21001:2018 (Educational Organization Management System/EOMS) implementation to the improvement of Islamic Religious Education (IRE) learning outcome quality in private Islamic junior secondary schools in Mataram City, West Nusa Tenggara. Employing a qualitative descriptive design, data were collected through semi-structured in-depth interviews and document analysis involving 30 informants comprising 12 IRE teachers and 18 Grade VIII–IX students from four purposively selected schools, two Integrated Islamic Junior Secondary Schools (SMP IT) and two private Islamic Junior Secondary Schools under the madrasah system (MTs). Thematic analysis facilitated by NVivo 15 generated 472 coding references across seven overarching themes, extracted from 387 pages of verbatim transcripts and 46 institutional documents. The findings reveal that the relevance of ISO 21001 to IRE learning outcome quality across cognitive, affective, and psychomotor dimensions operates through three mutually reinforcing mechanisms: (1) the standardization of instructional processes as a foundation for quality consistency; (2) data-driven evaluation systems as drivers of continuous improvement; and (3) the synergy between Islamic educational values itq?n and am?nah and EOMS principles as a multiplier effect. The school demonstrating the highest degree of EOMS principal internalization (S-1) recorded mean IRE scores of 88–90 across all three dimensions, compared to 70–77 at the school with the lowest internalization (S-4). Although none of the schools had obtained formal ISO 21001 certification, all exhibited varying degrees of principal adoption along a spectrum of implementation intensity. Theoretically, this study constructs a conceptual bridge between Islamic educational quality management theory and the international EOMS framework, while generating contextually grounded, tiered policy recommendations for private Islamic junior secondary schools in non-metropolitan Indonesian cities within the broader agenda of SDG 4.